2004
DOI: 10.1074/jbc.m311104200
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Small Heat Shock Protein Subunits and Substrate in Small Heat Shock Protein-Substrate Complexes

Abstract: Small heat shock proteins (sHSPs) are dynamic oligomeric proteins that bind unfolding proteins and protect them from irreversible aggregation. This binding results in the formation of sHSP-substrate complexes from which substrate can later be refolded. Interactions between sHSP and substrate in sHSP-substrate complexes and the mechanism by which substrate is transferred to ATP-dependent chaperones for refolding are poorly defined. We have established C-terminal affinity-tagged sHSPs from a eukaryote (pea HSP18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
116
1
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(120 citation statements)
references
References 40 publications
1
116
1
2
Order By: Relevance
“…It has been demonstrated that at substrate denaturing temperatures the equilibrium between the oligomeric and dimeric form of PsHsp18.1 and a number of other sHSPs is shifted toward the dimer (2,10), suggesting this is the substrate-binding species. For other sHSPs increased temperatures result in more rapid subunit exchange, which would also facilitate binding to a suboligomeric species (35,36). Because of difficulties in observing the sHSPsubstrate interaction at high temperatures, substrate bound to a dimeric or other suboligomeric sHSP form has not been observed directly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that at substrate denaturing temperatures the equilibrium between the oligomeric and dimeric form of PsHsp18.1 and a number of other sHSPs is shifted toward the dimer (2,10), suggesting this is the substrate-binding species. For other sHSPs increased temperatures result in more rapid subunit exchange, which would also facilitate binding to a suboligomeric species (35,36). Because of difficulties in observing the sHSPsubstrate interaction at high temperatures, substrate bound to a dimeric or other suboligomeric sHSP form has not been observed directly.…”
Section: Discussionmentioning
confidence: 99%
“…PsHsp18.1 single site mutants were generated using the Strategene quick change method (Stratagene) using a plasmid containing PsHsp18.1 with a C-terminal Strep tag (36). An amber stop codon was introduced at the desired position for Bpa incorporation and the mutant construct was transformed into BL21 E. coli cells along with the pSup-BpaRS-6TRN plasmid which was a generous gift from Dr. Peter Schultz (Scripps Institute, CA) (24).…”
Section: Methodsmentioning
confidence: 99%
“…Proteins with the Hsp18.1 N Terminus Protect Luc More Efficiently than Those with the Hsp16.9 N Terminus-As mentioned previously, we observed that Hsp18.1 is more effective than Hsp16.9 in protecting firefly Luc against heat insolubilization (14,15,21). To determine whether this difference could be due to differences in the N terminus, the wild-type and chimeric proteins were compared for their ability to protect Luc from insolubilization during heating.…”
Section: Journal Of Biological Chemistry 39945mentioning
confidence: 99%
“…This Hsp16.6-strep strain is fully isogenic to our wild-type strain, with the exception of the C-terminal tag on Hsp16.6. We have shown previously that the affinity tag does not significantly affect growth or viability under control or heat stress conditions compared with the wild-type strain (63). Wildtype Hsp16.6, ⌬hsp16.6, and Hsp16.6-strep cells were treated as described for the immunoprecipitation experiments (Fig.…”
Section: Hsp166-associated Proteins Represent Proteins That Become Imentioning
confidence: 99%